Present Status of Major Pests and Diseases of Tomato and Chili in Bali - I PUTU SUDIARTA; KETUT SUMIARTHA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2012)
ABSTRACT Present Status of Major Pests and Diseases of Tomato and Chili in Bali The research on the distribution of pests and diseases of tomato and pepper plants do to find out the latest situation on the type and spread of pests and diseases of those plants in the wet season in Bali. Methods of research were conducted by survey and identification method based on the symptoms of the disease in field and laboratory observations using microscope. The study was conducted in February 2012 in the planting center area of tomatoes and peppers in Ubud and Kintamani Bangli. The study was funded by AVRDC-The World Vegetable Center (USAID). The survey results show that the identification of major diseases of pepper plants is viruses, anthracnose (Colletotrichum acutatum) and Phytophthora capsici; whereas for tomato plants are dominated by Late Blight (Phytophthora sp.) and viruses. The diseases are found in almost all locations of planting tomatoes and peppers in Tabanan (Sandan, Bangli, Titi Galar, and Batu Sesa) and Bangli District (Katung, Bayung, Kedisan, and Abang Batu Dinding Wall). However each of the diseases attack intensity is different. The highest attack of anthracnose occurred at Galar Titi and Batu Sesa (Tabanan), while the highest virus infection was found in Kedisan and Abang Batu Dinding (Kintamani). Keywords: pests and diseases, tomatoes, peppers